2017
DOI: 10.1104/pp.17.01169
|View full text |Cite
|
Sign up to set email alerts
|

MiR408 Regulates Grain Yield and Photosynthesis via a Phytocyanin Protein

Abstract: Increasing grain yield is the most important object of crop breeding. Here, we report that the elevated expression of a conserved microRNA, OsmiR408, could positively regulate grain yield in rice () by increasing panicle branches and grain number. We further showed that OsmiR408 regulates grain yield by down-regulating its downstream target, , which is an uclacyanin (UCL) gene of the phytocyanin family. The knock down or knock out of also increases grain yield, while the overexpression of results in an opposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 43 publications
(65 reference statements)
6
108
0
1
Order By: Relevance
“…The expression levels of some miRNAs were changed in the OsAGO17 transgenic plants, such as OsmiR156j, OsmiR396c, OsmiR398b and OsmiR408, all of which have been reported to regulate seed development in rice (Jiao et al ., ; Zhang et al ., ,b), so there may be a complex regulatory network associated with OsAGO17. In addition, OsmiR397, OsmiR398 and OsmiR408 also play an important role in abiotic and biotic stress responses (Jia et al ., ; Lu et al ., ; Pan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The expression levels of some miRNAs were changed in the OsAGO17 transgenic plants, such as OsmiR156j, OsmiR396c, OsmiR398b and OsmiR408, all of which have been reported to regulate seed development in rice (Jiao et al ., ; Zhang et al ., ,b), so there may be a complex regulatory network associated with OsAGO17. In addition, OsmiR397, OsmiR398 and OsmiR408 also play an important role in abiotic and biotic stress responses (Jia et al ., ; Lu et al ., ; Pan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been identified as important regulators of grain size and yield in rice; among these miRNAs, miR397, miR398 and miR408 positively regulate grain size (Zhang et al ., , ,b). AGO is an essential protein that is involved in gene expression regulation through miRNAs (Bartel, ), and it is highly likely that at least one AGO protein is involved in grain size regulation in rice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a series of genetic manipulations of miR408 in rice have been reported (Zhang et al ; Zhou et al ). It was observed that overexpression of miR408 in rice could positively regulate grain yield via a phytocyanin protein (Zhang et al ). Our reported effects of miR408 in rice are consistent with this previous work.…”
Section: Discussionmentioning
confidence: 99%